ELITE LOKAL DAN POLITIK ELEKTORAL: Relasi Kuasa Perbanditan Sosial dalam Pemenangan Kontestan pada Pemilihan Kepala Daerah di Wilayah Tapal Kuda Jawa Timur - Darsono - Darsono; Basa Alim Tualeka; Aam Waro’ Panotogomo; Moh. Ali Shulthoni (Universitas Wijaya Kusuma Surabaya, 2026)
Local head elections in Indonesia are not merely arenas of formal competition among candidates but also involve informal actors who play strategic roles in mobilizing political support. This study aims to analyze the power relations among candidates, local elites, and voters in electoral politics in the Tapal Kuda region of East Java, employing the perspectives of social banditry as developed by Eric Hobsbawm and the concept of moral economy proposed by James C. Scott. This research adopts a qualitative approach within an interpretive paradigm and applies a descriptive-ethnographic method. Data were collected through in-depth interviews, observations, and document analysis in Jember, with additional data from Situbondo and Banyuwangi. Informants include electoral candidates, campaign teams, local elites (such as kyai, religious leaders, local strongmen, and business actors), as well as voters. The findings reveal that local elites function as political brokers who mediate the relationship between candidates and voters through transactional mechanisms that, in many cases, evolve into forms of social banditry. These practices are not only related to the distribution of political resources but are also socially legitimized through moral-economic values. The resulting power relations are symbiotic in nature but produce structural consequences, including high-cost politics, the dependency of elected leaders on elite networks, and the weakening of local democratic quality.